Analysis of the functioning computer equipment under the influence of electromagnetic interference through the power supply network - Z. M. Gizatullin; R. M. Gizatullin; I. N. Ziatdinov (Известия высших учебных заведений: Проблемы энергетики)
The paper deals with experimental studies of noise immunity of computer technology in electromagnetic effects on the power supply. The results of quantitative studies functioning computer equipment when exposed to electromagnetic pulses on the mains and compared with the simulation results. The results of studies of the effectiveness of external protection devices computer equipment under the influence of electromagnetic pulses on the mains are presented. The reported study was supported by RFBR, research project No. 14-01-31108 мол_a”.